Aplicação de membranas cerâmicas no tratamento de efluentes têxteis - Batista, Felipe Peixoto Mangueira (2019)
The environmental and social impacts of the degradation of water quality due to anthropogenic action have increased alarmingly over the years. Due to the complexity of contaminants, textile effluents are considered very harmful to the environment, and their proper disposal is a current concern. The general objective of this work was to evaluate the efficiency of ceramic membranes based on clay and sugarcane bagasse ash in the treatment of textile effluents from industries in the metropolitan area of João Pessoa, PB. For this purpose, the raw materials used in the preparation of the membranes were characterized by thermal, chemical and mineralogical analysis. The physical properties water absorption, apparent porosity, apparent density, water permeability and microstructural characteristics of the obtained membranes were determined. The functionality of the membranes for the treatment of the collected effluents was evaluated by comparing the physicochemical parameters of color, turbidity, Total Suspended Solids (TSS), Total Dissolved Solids (TDS) and Chemical Oxygen Demand (COD), determined for the effluents, before and after filtration. The ceramic membrane presented an apparent porosity of 25.76%, highly porous surface and water permeated flow, at a pressure of 200 kPa, of 500 L/h.m2. On the three effluents analyzed, two obtained very significant results, in which, the treatment presented efficiency of removal of five of the six parameters ranging from 82 to 96%. However, for one of the effluents, only two parameters showed removal efficiency between 50 and 60%. It was concluded that the application of the ceramic membranes studied is feasible as a pre-treatment of industrial textile effluents, in view of the significant reduction of their polluting potential. Another very positive point is the possibility of using membranes of low relative cost, since they were made with abundant natural raw material and industrial wastes.